TRANSFORMASI NOVEL LASKAR PELANGI KARYA ANDREA HIRATA KE FILM LASKAR PELANGI KARYA SUTRADARA RIRI RIZA - Hastuti Hastuti; Supriyono Supriyono (LPPM STKIP PGRI Bandar Lampung, 2021)
This study aims to describe the transformations of plot and characterization from the novel Laskar Pelangi to the film Laskar Pelangi by using the ecranization method. This research is a qualitative descriptive study. The research focuses on the transformations of plot and characterizations from the novel Laskar Pelangi (verbal) to the film Laskar Pelangi (audio visual). The data were obtained by reading the novel thoroughly and repeatedly, listening to the film and then identifying and comparing aspects of the plot and characters between the two works so as to find similarities and differences between the works and then record the changes that occurred, especially the plot and characters. Data were analyzed by inductive comparative analysis technique and ecranization process. The validity of the data was obtained through semantic validity and reliability (interrater and intrarater). The results showed that: (1) the transformation of the plot from the novel to the Laskar Pelangi film is that there is a difference in the plot through the addition of film scenes, the reduction of the story in the novel but not shown in the film, and variations in the film compared to the original novel, ( 2) the transformation of characterizations from novels to films caused several changes, such as the omission of Drs. Zulfikar, the appearance of the new characters Pak Mahmud, Pak Zulkarnaen, and Pak Bakri.